2007 IEEE International Electron Devices Meeting 2007
DOI: 10.1109/iedm.2007.4418955
|View full text |Cite
|
Sign up to set email alerts
|

Drain Corrosion in RF Power GaAs PHEMTs

Abstract: Si02Suc ri We have investigated drain degradation in a set of passivation Source G Drain experimental RF power GaAs PHEMTs. Drain degradation ohmics_ was observed in the form of an increase in RD and aca reduction in Imax in a variety of conditions. We found that tcGhstA both forms of degradation arise from surface corrosion that AIGaAs takes place on different locations on the drain and chantne dominate in different regimes of operation. Specifically, AIGaAs the increase in RD was prominent in the ON-state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…A consequence of this is to produce a change in the pattern of degradation, as the experiment advances with the edges lighting up as the stress voltage is increased. Separately, in these devices, we have found that the main electricaldegradation mechanism under the conditions studied in this paper is corrosion of the n+ GaAs cap on the drain side of the device [6], [7]. We also found that this mechanism is strongly driven by electric field and temperature.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…A consequence of this is to produce a change in the pattern of degradation, as the experiment advances with the edges lighting up as the stress voltage is increased. Separately, in these devices, we have found that the main electricaldegradation mechanism under the conditions studied in this paper is corrosion of the n+ GaAs cap on the drain side of the device [6], [7]. We also found that this mechanism is strongly driven by electric field and temperature.…”
Section: Resultsmentioning
confidence: 85%
“…The reduction in light emission for constant V DS in the late stages of the experiment indicates a reduction in impact ionization that is probably due to R D degradation decreasing the intrinsic V DG that is applied to the device [12]. R D degradation is a consequence of the aggressive electrical stress applied to this device [6], [7], [14]. 2 shows light-emission images obtained at various times during the experiment.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…We have previously reported a comprehensive study of degradation of AlGaAs/InGaAs PHEMTs during operation under high humidity conditions [3,4]. We have concluded that PHEMT degradation is caused by an electrochemical corrosion reaction between the semiconductor and H 2 O that takes place at the SiN x /semiconductor interface on the drain side of the device.…”
Section: Introductionmentioning
confidence: 99%